2014
DOI: 10.4067/s0718-58392014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Cacao in Mexico: restrictive factors and productivity levels

Abstract: Cacao (Theobroma cacao L.) represents one of the most important agricultural crops of the humid Mexican tropics. In the last 10 yr, approximately 23.000 t of this grain were no longer produced per cycle. The objective of this study was to identify characteristics and factors that restrict production in the states of Tabasco and Chiapas. A survey was applied to obtain information about 184 producers and their plantations by two-stage sampling. Descriptive statistics were calculated and multilevel models were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Integrated disease management can be economically sustainable (Díaz‐José et al ., ; Krauss et al ., ; Soberanis et al ., ). Unfortunately, farmer outcomes vary, influenced by individual efficiencies, the cacao germplasm and the local environment.…”
Section: Disease Managementmentioning
confidence: 99%
“…Integrated disease management can be economically sustainable (Díaz‐José et al ., ; Krauss et al ., ; Soberanis et al ., ). Unfortunately, farmer outcomes vary, influenced by individual efficiencies, the cacao germplasm and the local environment.…”
Section: Disease Managementmentioning
confidence: 99%
“…and the branch galls (Fusarium sp.) (Córdova-Ávalos et al, 2001, Díaz-José et al, 2014, Hernández-Gómez et al, 2015.…”
Section: Socioecological Autoregulationmentioning
confidence: 99%
“…Nevertheless, there are other peasants that don´t use those biotic resources for selfconsumption or sale even if they know their uses (Bautista-Mora et al, 2016). Finally, the incomes generated by the cacao production can be complemented with other activities, like other crops, salaried work on the cities and the commerce (Chávez- García, 2012, Díaz-José et al, 2014, Hernández-Gómez et al, 2015, López-Cruz et al, 2021.…”
Section: Capitalmentioning
confidence: 99%
“…Cocoa yield remains under the latter potential level due to: (i) an inadequate cropping system mainly consisting of full-sun monocultures without shade, leading to soil erosion, nutrient depletion, water shortages, weed growth, and increased pest and disease outbreaks [7][8][9][10][11]; and (ii) inadequate pest and disease management [12,13]; both leading to (iii) below-optimum pollinator population levels. Earlier research showed that increasing pollination, either manually [14] or indirectly by improving breeding opportunities for pollinating midges [14][15][16], had a significant impact on cocoa yield compared with normal agricultural practices control plots.…”
Section: Introductionmentioning
confidence: 99%